(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Emblica officinalis popularly known as Amalaki and Indian Goose Berry in English belongs to family Euphorbeaceae. Amalaki is gift of nature to mankind and is known as Amritphala in Sanskrit which means â€œFruit of Heavenâ€. Amalaki is widely distributed in tropical and subtropical areas and has therapeuticpotential against deleterious diseases. Earlier it becomes a notable fruitfor its rich amount of vitamin C, polyphenols such as tannins, gallicacid, ellagic acid, flavonoids like quercetin and rutin. Emblica officinalis (Amla) are widely used in the Indian system of medicineand believed to increase defense against diseases. Emblica officinalis is a versatile plant due to its various medicinal properties. Emblica officinalis seeds, leaves and fruits are commonly used for medicinal purpose. The various medicinal properties of Emblica officinalis such as Antioxidant, Antipyretic, Analgesic, Cytoprotective, Anti-ulcer, Immune modulatory, Anti Inflammatory, Antitussive and Gastro-protective have been studied. Emblica officinalis having a strong Memory enhancing property, cholesterol lowering, applicable in ophthalmic disorder, are reviewed. The effects of Emblica officinalis also take account as an Antimicrobial action and in neutralizing snake venom are also included. It is used as a single remedy and as content in many medicinal preparations. The current review is to summarize Description, Phytochemistry, Therapeutic Activity, Pharmacological Activity of Emblica officinalis, which may be helpful to establish a Standard Natural drug as an Antimicrobial.